Immobilization of Ni(II) on Amine-Functionalized Mesoporous Silica as Catalyst for Benzyl Alcohol Acetylation Reaction - Nabilah, Wardah; Kunarti, Eko Sri; Pambudi, Fajar Inggit (Makara Journal of Science, 2024)
In this study, amine-functionalized and Ni(II)-immobilized mesoporous silica materials were synthesized. This research aimed to synthesize mesoporous silica based on rice husk ash functionalized with amine and immobilized with Ni(II). The activity of amine-functionalized and Ni(II)-immobilized mesoporous silica materials was studied for the acetylation of benzyl alcohol with acetic anhydride as the acetylating agent. First, mesoporous silica was synthesized using rice husk ash using the sol–gel method, followed by amine functionalization using (3-aminopropyl)triethoxysilane (APTES) and Ni(II) immobilization through ultrasonic treatment. The results obtained showed that amine-functionalized and Ni(II)-immobilized mesoporous silica (SiO2/APTES/Ni(II)) were successfully synthesized, confirmed by Fourier transform infrared and Energy-dispersive X-ray spectrometry data. In addition, the synthesized materials had an average pore diameter of 12.83 nm. Afterward, the catalytic activity test showed that SiO2/APTES/Ni(II) was able to convert 98.34% of benzyl alcohol in the acetylation reaction at 45 °C for 5 h. The use of the SiO2/APTES/Ni(II) catalyst for three cycles obtained percent conversion values with a slight decreases (98.34%, 95.20%, and 90.61%).